The causal effect of inflammatory bowel disease on diffuse large B-cell lymphoma: two-sample Mendelian randomization study - Lu, Chuanyang; Chen, Qiuni; Tao, Hong; Xu, Lei; Li, Jiaxin; Wang, Chunling; Yu, Liang (Frontiers in Immunology, 2023)
Background: It has been reported that inflammatory bowel disease (IBD) is associated with an increased risk of malignancies, including lymphoma. A number of large observational studies have been devoted to exploring the causal link between IBD and malignant lymphoma. However, no consensus exists on whether there is a causal relationship between IBD and malignant lymphoma.The summary data set of the IBD and lymphoma genome-wide association studies (GWAS) were obtained from the OPEN GWAS website. Single nucleotide polymorphisms (SNPs) were selected as genetic instrumental variants (IVs) for fulling p<5×10 -8 and linkage disequilibrium [LD] of r 2 =0.001 in the IBD GWAS. The proxy SNPs with LD of r 2 >0.8 were identified. The palindromic SNPs and outlier SNPs were excluded. The assessments of sensitivity were employed by the Cochran's Q test, MR-Egger intercept test and leave-one-out analysis.The MR analysis results proved that the causality of IBD on DLBCL. The risk of developing DLBCL is increased by 28.6% in patients with IBD (ORIVW=1.286, 95%CI 1.066-1.552, P=0.009). The results of the subgroup analysis showed that Crohn's disease (ORIVW=1.218, 95%CI 1.030-1.441, P=0.021) rather than ulcerative colitis (ORIVW=1.206, 95%CI 0.984-1.478, P=0.072) had a causal effect on DLBCL.And no horizontal and directional pleiotropy were observed in the MR studies.The above MR study concluded that IBD itself is causally responsible for DLBCL, especially Crohn's disease. Further investigations are needed to elucidate the mechanism underlying this direct causal link.